Measuring spatiotemporal accessibility and equity of emergency medical services in Shanghai, China - Haolin Zhu; Mo Xu; Luying Zhu (PLoS ONE, 2025)
Emergency Medical Services (EMS) are a critical component of public healthcare. This study aimed to precisely measure the spatiotemporal accessibility and equity of EMS in Shanghai. We constructed a research model that combines web mapping application programming interfaces (APIs) and empirical Bayesian kriging (EBK) interpolation methods to calculate EMS accessibility, and used the Theil index to assess the equity of EMS accessibility. Additionally, we used the Minimum Cumulative Resistance (MCR) Model to evaluate the rationality of EMS stations layout. The results indicated that the per capital response time (PRT) in Shanghai increased from 11.46 minutes during smooth traffic periods to 13.08 minutes during peak traffic periods, and the 12 min EAI population coverage rate dropped from 60.6% to 41.9%. Thile index results demonstrated that there is significant inequity in Shanghai’s EMS, primarily driven by the disparity in accessibility between central and suburban districts. The results based on the MCR model indicated that the EMS stations in central districts had smaller shortest-time service areas, fewer resource demands, and lower PRTs. Obtained results revealed that EMS accessibility in Shanghai exhibited clear spatiotemporal variation, driven by disparities across urban districts and multi-period traffic conditions. Additionally, the irrational layout of EMS stations exacerbated the equity and opportunity to EMS services for citizens in suburban districts of Shanghai.